Impaired β Cell Function in Chinese Newly Diagnosed Type 2 Diabetes Mellitus with Hyperlipidemia. (14th April 2014) - Ma, Yuhang; Wang, Yufan; Huang, Qianfang; Ren, Qian; Chen, Su; Zhang, Aifang; Zhao, Li; Zhen, Qin; Peng, Yongde
Abstract : The objective is to explore the effects of hyperlipidemia on β cell function in newly diagnosed type 2 diabetes mellitus (T2DM). 208 patients were enrolled in the study and were divided into newly diagnosed T2DM with hyperlipidemia (132 patients) and without hyperlipidemia (76 patients). Demographic data, glucose levels, insulin levels, lipid profiles, homeostasis model assessment for β cell function index (HOMA- β ), homeostasis model assessment for insulin resistance index (HOMA-IR), and quantitative insulin-sensitivity check index (QUICKI) were compared between the two groups. We found that comparing with those of normal lipid levels, the subjects of newly diagnosed T2DM with hyperlipidemia were younger, and had declined HOMA- β . However, the levels of HOMA- β were comparable regardless of different lipid profiles (combined hyperlipidemia, hypertriglyceridemia, and hypercholesterolemia). Multiple stepwise linear regression analysis showed that high fasting plasma glucose (FPG), decreased fasting insulin level (FINS), and high triglyceride (TG) were independent risk factors of β cell dysfunction in newly diagnosed T2DM. Therefore, the management of dyslipidemia, together with glucose control, may be beneficial for T2DM with hyperlipidemia.